Pengaruh Media Pembelajaran Multimedia Berbasis Flash Player Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Fiqh Kelas V Di Madrasah Ibtidaiyah Muhammadiyah 15 Banjarwati Paciran. - M. Chotibuddin (STIT Muhammadiyah Paciran Lamongan, 2022)
: The application of media in the learning process is one way that can be used to realize achievement and learning outcomes. Because learning media is one thing that absolutely exists in the learning process. Interactive multimedia-based learning is one source of learning based on Information and Communication Technology (ICT). The purpose of this research was to analyze the effect of flash player-based multimedia learning media on learning outcomes. Students in the fifth grade on Fiqh subject at MI Muhammadiyah 15 Banjarwati Paciran.The research design used is One Groups Pretest-Posttest Design with saturated sample sampling technique. The number of samples is 22.The results showed that the average prettest score (before being given the media) was (60.23) while the posttest average was (69.55). According to the t-test calculation, it was obtained tcount (5.52) > ttable (2,086), so it can be said that the flash player-based multimedia learning method is effective and significant on student learning outcomes in the subject matter of Hajj in the fifth grade at MI Muhammadiyah 15 banjarwati paciran for the academic year 2020/2021.This proves that there is difference between learning outcomes in Fiqh subjects on the subject matter of Hajj before and before using multimedia-based learning media using Adobe Flash.